PRE-ALEXANDROFF SPACE - Al-Badry, Ayed .E. Hashoosh (University of Thi-Qar Journal of Science, 2013)
In this paper we introduce a new definition of the topological space weaker of Alexandroff space, namely pre-Alexandroff space. These spaces are which arbitrary intersection of an open set is a pre-open set. In addition to give a new definition of minimal pre-open sets and investigate about some of its properties, also we get some theorems and result related to this space.